Research on the method of extrapolating 3D particle profile from 2D Fourier spectrum. Issue 2 (April 2021) - Zheng, Shanxi; Zheng, Jiagen; Guo, Xia; Sun, Bingqi; Shi, Chong
Abstract: Based on 2D Fourier analysis, a shape extrapolation method of 3D geotechnical particles with arbitrary roughness is proposed, and the control conditions are discussed. It is realized that the two-dimensional profile is randomly constructed by Fourier description, then the three-dimensional particles are extrapolated using the profiles of multiple sections, lastly the 3D random particles can be generated which are close to the actual particle's area, volume, roundness and other morphological characterization parameters; and particles with different accuracy can be constructed by controlling the number of sections. This method can provide help for the discrete element numerical calculation of particles.